Angiotensin System Blockade Combined With Calcium Channel Blockers Is Superior to Other Combinations in Cardiovascular Protection With Similar Blood Pressure Reduction: A Meta‐Analysis in 20, 451 Hypertensive Patients. Issue 8 (17th January 2016) - Chi, Chen; Tai, Chenhui; Bai, Bin; Yu, Shikai; Karamanou, Marianna; Wang, Jiguang; Protogerou, Athanase; Blacher, Jacques; Safar, Michel E.; Zhang, Yi; Xu, Yawei
Abstract : The authors aimed to investigate the superiority of angiotensin system blockade (angiotensin‐converting enzyme [ACE] inhibitor/angiotensin receptor blocker [ARB]) plus a calcium channel blocker (CCB) (A+C) over other combination therapies in antihypertensive treatment. A meta‐analysis in 20, 451 hypertensive patients from eight randomized controlled trials was conducted to compare the A+C treatment with other combination therapies in terms of blood pressure (BP) reduction, clinical outcomes, and adverse events. The results showed that BP reduction did not differ significantly among the A+C therapy and other combination therapies in systolic and diastolic BP ( P =.87 and P =.56, respectively). However, A+C therapy, compared with other combination therapies, achieved a significantly lower incidence of cardiovascular composite endpoints, including cardiovascular mortality, nonfatal myocardial infarction, and nonfatal stroke (risk ratio [RR], 0.80; 95% confidence interval [CI], 0.70–0.91; P <.001), but similar all‐cause mortality (RR, 0.90; 95% CI, 0.77–1.04; P =.15) and stroke rates (RR, 0.90; 95% CI, 0.77–1.04; P =.09). Moreover, A+C therapy yielded a 4.21 mL/min/1.73 m 2 lower estimated glomerular filtration rate reduction than other combinations ( P <.001). Finally, A+C therapy showed a similar incidence of adverse events as other combination therapies ( P =.34) but presented a significantly lower incidence of serious adverse events (RR, 0.85; 95% CI, 0.73–0.98; P =.03). In conclusion, A+C therapy is superior to other combinations of antihypertensive treatment as it shows a lower incidence of cardiovascular events and adverse events, while it has similar effects in lowering BP and preserving renal function.